The Predicate Semantic with Linguists An Anajytical Study - Naseer Thojeel Dawood ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The study deals with the definition of the predicate ــ according to the rationalists ( the logicians ) and Akhbaris (the linguists and fundamentalists ) ــ an analytical study ، with mentioning its most prominent nomenclature، its types ، the criterion of truthfulness and falsehood in it ، and the opinions of the two teams on the difference between complete and incomplete predicate ، as well as the sections of the sentence as an analysis and discussion، We come to the conclusion that the fundamentalists search was an in-depth study that seeks to delve into the depths of the sentence in order to examine it، and reveal its hidden connotations . And this is what made one of the scholars to describe the grammatical research of the fundamentalists as (semantics). DOI /10.54633/2333-021-042-015